Analysing the potential of industrial tourism for Karawang and the socio-economic impact - Rastri Kusumaningrum; Firdaus Yuni Dharta; Chaerudin (Faculty of Communications Science, Dr. Soetomo University, 2023)
Karawang is the largest industrial area in Indonesia. It lies in proximity to the capital, Jakarta, encompassing a vast expanse of 13,756,358 hectares dedicated to industrial use. Geographically situated along the bustling Transjava route, it enjoys accessibility through various modes of public transportation. Despite these advantages, Karawang remains relatively unknown in the tourism industry. The development of tourism is intrinsically tied to the concept of identity, where the intricate interplay between tourism and identity assumes growing importance due to the complexity of identity itself. Tourism identity represents the unique characteristics of a region that set it apart from other tourist destinations. The nexus between these two factors can significantly contribute to establishing a city's brand. Field research reveals that Karawang's industrial assets hold the potential to be harnessed for industrial tourism, potentially becoming an integral element of its tourism identity. This study seeks to ascertain the perspectives of the local government in Karawang regarding the development of tourism identity to bolster the city's branding. Employing a case study approach, this article explores the governmental strategies for shaping the city brand of Karawang in the context of industrial tourism. The research findings offer valuable insights and recommendations to strengthen Karawang's distinctive identity.